Quo Vadis of Politics of Law of Human Rights Protection Policy in Indonesia - Anif, Virdatul (Universitas Negeri Semarang, 2017)
Human rights are considered as something very fundamental, which are strictly regulated in both national and international legal instruments. Issues regarding the protection of human rights have always been the concern of many parties, including the fulfillment of the rights themselves. The fulfillment and protection of human rights, although universally regulated, is still heavily influenced by the ideology of a country and even the policies of the government regime. This paper discusses the direction of legal politics in human rights protection policies in Indonesia from time to time. This paper attempts to look at the politics of law in the light of the policies and laws and regulations that have been made related to human rights in Indonesia.